From Waste to Wealth: Advancing Sustainability and Social Equity through Circular Economy Models - Mohd Salleh, Norlida Hanim; Wijijayanti, Trisetia; Hamzah, Noradiva; Jauhari, Azmafazilah; Mansur, Mustazar; Mafruhah, Izza (European Journal of Sustainable Development, 2025)
This paper explores the potential of waste-to-wealth economies initiatives within the circular economy framework to promote environmental sustainability and reduce socio-economic inequalities. It highlights how traditional linear economic models contribute to resource depletion and pollution, disproportionately impacting marginalized communities. By transforming waste into valuable resources, waste-to-wealth strategies can generate new economic opportunities, improve environmental conditions, and foster social inclusion for underserved populations. The paper introduces a conceptual framework linking circular economy principles with resource and social justice to ensure equitable access and benefit-sharing. It also examines challenges such as power imbalances, technological gaps, market barriers, and fragmented policies that may hinder inclusive implementation. Ultimately, the study emphasizes the need for coherent, justice-oriented policies and community engagement to realize a circular economy that supports both sustainable development and social equity. Keywords: waste-to-wealth, inequality, circular economy, inequality, economic opportunities, empowerment, policy.